KEBIJAKAN PENATAAN PASAR PEMERINTAH DAERAH DAN PENETAPAN KAWASAN PEDAGANG KAKI LIMA PASAR PERBATASAN - Imam Fadly Ikhsani E.42008017 (FISIP Universitas Tanjungpura Pontianak, 2012)
The purpose of thesis writing is to determinate about management policy and complication in Entikong border markets, the title of thesis based on problem in Entikong border traditional markets, where the issue concernsthe sellers who sell in the market initially surprised Entikong Serikin exodus to the region (Malaysia) and sell there. Where problems arise after the market was moving within ± 500 meters from its original place. Conclusions in this study is the presence of many factors inhibiting the implementation of policies in which one of them is unsyncronized actors and policy makers in decision making where the actors involved more emphasis on sectoral ego respectively. So that no one thought the future expected generated jointly so that the implementation of the policy can work well and deliver positive results for society, government, state and nation. Keywords: Public Policy, Public Policy Implementation, Border Market